Au@Pd Core–Shell Nanobricks with Concave Structures and Their Catalysis of Ethanol Oxidation. Issue 10 (8th August 2013) - Wang, Wenjin; Zhang, Jie; Yang, Shengchun; Ding, Bingjun; Song, Xiaoping
Abstract Au@Pd core–shell nanobricks (CNBs) with concave surfaces and Pd shells with a thickness of approximately 5 nm were synthesized by co‐reduction of HAuCl4 and H2PdCl4 in the presence of Au seeds and Ag ions. These as‐synthesized concave CNBs exhibit significantly enhanced catalytic activity for the electrooxidation of ethanol in alkaline media compared to the commercially‐used Pd black. The improved performance of the Au@Pd CNBs can be attributed to the exposed stepped surfaces, high‐index facets, and the synergistic effects of the core and shell metals.